Gene loops enhance transcriptional directionality - Tan-Wong, Sue Mei; Xu, Zhenyu; Steinmetz, Lars M. (Science. First release, 2012)
Eukaryotic genomes are extensively transcribed, forming both messenger RNAs (mRNAs) and noncoding RNAs (ncRNAs). ncRNAs made by RNA polymerase II often initiate from bidirectional promoters (nucleosome-depleted chromatin) that synthesize mRNA and ncRNA in opposite directions. We demonstrate that, by adopting a gene-loop conformation, actively transcribed mRNA encoding genes restrict divergent transcription of ncRNAs. Because gene-loop formation depends on a protein factor (Ssu72) that coassociates with both the promoter and the terminator, the inactivation of Ssu72 leads to increased synthesis of promoter-associated divergent ncRNAs, referred to as Ssu72-restricted transcripts (SRTs). Similarly, inactivation of individual gene loops by gene mutation enhances SRT synthesis. We demonstrate that gene-loop conformation enforces transcriptional directionality on otherwise bidirectional promoters. A protein constrains double-helical DNA physically, thereby pointing RNA polymerases in the right direction. A protein constrains double-helical DNA physically, thereby pointing RNA polymerases in the right direction.